Structural, Opticaland Morphological Properties Of Zn And Mg Co-Doped V2O5 Thin Filmnanostructures (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research study reveals metallic co-doping of Zinc(Zn) and Magnesium (Mg) on vanadium pentoxide(V2O5) thin ﬁlm nanostructures by spray pyrolysis deposition technique. The studyfindings have been made into how the morphological, structural and optical properties of the materials change for the different co-doping percentage of 1%,3%,5%10% of Zn-Mg. X-ray diffraction (XRD)clearly showsan orthorhombic crystalline structure with polycrystalline nature.The dopantZn and Mginfused into the V2O5 matrixand is confirmed by EDAX images. A field emission scan electron microscope was used to examine surface morphology whichreveals that grain structure has beenmodified by increasing the doping content. It is evident from theatomic force microscopy (AFM) images that the effect of Zn and Mg on V2O5 thin filmshave enhanced surface roughness.The transmittance and energy bandgap (Eg) of the film found to be decreased with an increase in doping concentration whereas absorbance varieswith doping levels.The research findings suggest that the Zn-Mg co-doped V2O5 thin films could be a potential source for energy,optical and sensor-based device applications.